2008
DOI: 10.1021/ja800835q
|View full text |Cite
|
Sign up to set email alerts
|

Pristine Simple Oxides as Visible Light Driven Photocatalysts: Highly Efficient Decomposition of Organic Compounds over Platinum-Loaded Tungsten Oxide

Abstract: Tungsten oxide loaded with nanoparticulate platinum is demonstrated to exhibit high activity for the decomposition of organic compounds both in liquid and gas phases; the activity was almost comparable to that of TiO2 under UV light irradiation and much higher than that of nitrogen-doped TiO2 under visible irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
507
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 746 publications
(544 citation statements)
references
References 19 publications
19
507
2
3
Order By: Relevance
“…Like hermatite, Tungsten trioxide, has the disadvantage of a low electron conduction band, although studies claim that coupling with Pt cocatalyst has been observed to be useful in promoting alternative multiple-electron reduction processes with lower reduction potentials. This has increased the use of WO 3 as one of the very few highly visible-light-active single-phase oxide photocatalysts [29][30][31][34][35][36][37][38][39][40][41].…”
Section: Photocatalyst Materials and Supportsmentioning
confidence: 99%
“…Like hermatite, Tungsten trioxide, has the disadvantage of a low electron conduction band, although studies claim that coupling with Pt cocatalyst has been observed to be useful in promoting alternative multiple-electron reduction processes with lower reduction potentials. This has increased the use of WO 3 as one of the very few highly visible-light-active single-phase oxide photocatalysts [29][30][31][34][35][36][37][38][39][40][41].…”
Section: Photocatalyst Materials and Supportsmentioning
confidence: 99%
“…The addition of the elements as a co-catalyst such as platinum / Pt, gold / Au and silver / Ag in the material WO3 reported to increase the activity of photocatalytic in the visible than WO3 pure [4][5][6]. Until right now, co-catalyst Pt is best able to increase the photocatalytic activity of WO3.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] PC oxidation for indoor air purification and self-cleaning is today considered in several applications in the built environment. 12,13 Recently, WO 3 has drawn attention because of its high efficiency in PC activity under daylight illumination [14][15][16][17] and its ability to photodegrade a wide range of environmental pollutants. 16,18,19 Nano-WO 3 is reported to have much higher PC activity compared to bulk WO 3 photoelectrodes.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recently, WO 3 has drawn attention because of its high efficiency in PC activity under daylight illumination [14][15][16][17] and its ability to photodegrade a wide range of environmental pollutants. 16,18,19 Nano-WO 3 is reported to have much higher PC activity compared to bulk WO 3 photoelectrodes. 5,20 This is related to the different mechanism of charge separation and charge transport in the nanocrystalline semiconductor films, which is a subject of continuing discussion.…”
Section: Introductionmentioning
confidence: 99%